Digital HRM Transformation Improves Employee Performance through Digital Competence - Irvan Rolyesh Situmorang; Petrus Loo (CV. Sakura Digital Nusantara, 2026)
Purpose – This study investigates how digital transformation in human resource management contributes to employee performance by emphasizing the role of digital competence within organizational work systems. The study is conducted in the context of organizations in Medan that have increasingly adopted digital-based HR practices. Design/methodology/approach – A quantitative explanatory approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires distributed to employees who had experience using digital HR systems, including electronic attendance, online training platforms, and digital performance evaluation systems. Finding/Results – The findings demonstrate that digital HRM transformation positively influences employee digital competence and employee performance. Digital competence also shows a significant contribution to improving employee performance. In addition, the mediation analysis confirms that digital competence partially mediates the relationship between digital HRM transformation and employee performance, indicating that technological implementation becomes more effective when supported by employees’ digital capabilities. Originality/Value – This study offers a broader understanding of digital transformation by positioning digital competence as a strategic organizational capability rather than merely an individual technical skill. The findings provide practical insights for organizations seeking to align technological transformation with human capability development in order to achieve sustainable performance improvement